Exposure to nanoplastics and nanomaterials either single and combined affects the gill-associated microbiome of the Antarctic soft-shelled clam Laternula elliptica - Rondon, Rodolfo; Cosseau, Celine; Bergami, Elisa; Cardenas, Cesar A.; Perez-Toledo, Carolina; Alvarez, Diego; Aldridge, Jacqueline; Font, Alejandro; Garrido, Ignacio; Santa Cruz, Francisco; Perrois, Garance; Balbi, Teresa; et al. (My University, 2024)
Nanoplastics and engineering nanomaterials (ENMs) are contaminants of emerging concern (CECs), increasingly being detected in the marine environment and recognized as a potential threat for marine biota at the global level including in polar areas. Few studies have assessed the impact of these anthropogenic nanoparticles in the microbiome of marine invertebrates, however combined exposure resembling natural scenarios has been overlooked. The present study aimed to evaluate the single and combined effects of polystyrene nanoparticles (PS NP) as proxy for nanoplastics and nanoscale titanium dioxide (nano-TiO2) on the prokaryotic communities associated with the gill tissue of the Antarctic soft-shell clam Laternula elliptica, a keystone species of marine benthos Wildcaught specimens were exposed to two environmentally relevant concentrations of carboxylated PS NP (PS-COOH NP, -62 nm size) and nano-TiO2 (Aeroxide P25, -25 nm) as 5 and 50 mu g/L either single and combined for 96h in a semi-static condition.Our findings show a shift in microbiome composition in gills of softshell clams exposed to PS NP and nano-TiO2 either alone and in combination with a decrease in the relative abundance of OTU1 (Spirochaetaceae). In addition, an increase of gammaproteobacterial OTUs affiliated to MBAE14 and Methylophagaceae (involved in ammonia denitrification and associated with low-quality water), and the OTU Colwellia rossensis (previously recorded in polluted waters) was observed. Our results suggest that nanoplastics and nano-TiO2 alone and in combination induce alterations in microbiome composition by promoting the increase of negative taxa over beneficial ones in the gills of the Antarctic soft-shell clam. An increase of two low abundance OTUs in PS-COOH NPs exposed clams was also observed. A predicted gene function analysis revealed that sugar, lipid, protein and DNA metabolism were the main functions affected by either PSCOOH NP and nano-TiO2 exposure. The molecular functions involved in the altered affiliated OTUs are novel for nano-CEC exposures.
Keywords: cecs; bivalve; prokaryotic; nanoplastic; titanium dioxide; microbiome; antarctica